Pengembangan Karakter Kepribadian Anak Usia Dini (Studi Pada PAUD Islam Terpadu Di Kabupaten Magelang Tahun 2015) - Jaka Siswanta (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
The purpose of this study is to describe the values developed in the development of the child’s personality character, describe the implementation of the development of children’s personality traits, the strategy of developing the personality character of children, the constraints in the implementation of the development of child personality character in the Integrated Islamic School of Magelang District 2015. With a qualitative approach using purposive sampling technique. The results pointed. PAUD Integrated Aisyiyah Insan Robbani Muntilan and Islamic Early Childhood Ibnu Hadjar refers to the provisions of the implementation of Character Education established by the Ministry of National Education, early childhood education developed values of personality traits based on the value determined by the school. Implementation of character formation is done as an effort to form the character of child’s personality. Character development strategy is done by the method of playing while singing, exemplary methods, methods of advice, methods of supervision and method of habituation. Constraints, especially parents support factors related to school policy in the development of children’s personality traits.